Elevated dopa decarboxylase activity in living brain of patients with psychosis. - Reith, J (1994)
The hypofrontality theory of the pathogenesis of schizophrenia predicts that cortical lesions cause psychosis. During a search for abnormalities of catecholaminergic neurotransmission in patients with complex partial seizures of the mesial temporal lobe, we discovered an increase of the rate of metabolism of an exogenous dopa tracer (6-[18F]fluoro-L-dopa) in the neostriatum of a subgroup of patients with a history of psychosis. When specifically assayed for this abnormality, patients with schizophrenia revealed the same significant increase of the rate of metabolism in the striatum. The finding is consistent with the theory that a state of psychosis arises when episodic dopamine excess is superimposed on a trait of basic dopamine deficiency in the striatum. The finding is explained by the hypothesis that cortical insufficiency, a proposed pathogenetic mechanism of both disorders, causes an up-regulation of the enzymes responsible for dopa turnover in the neostriatum as well as the receptors mediating dopaminergic neurotransmission.